STANDARISASI TAHSIN GURU UNTUK PENINGKATAN KELULUSAN UJIAN TAHSIN SISWA SDIT SALSABILA 2 KLASEMAN SLEMAN - Ahmad Safii; M. Rofi Fauzi (Fakultas Tarbiyah, IAIN Fattahul Muluk Papua, 2024)
How to read the Qur'an in one educational institution if it is not standardized will cause obstacles. The Qur'an has a variety of ways of reading (qiro'at), among which are qiro'at sab'ah (seven) and 'asyroh (ten). In Indonesia qiro'at masyhuroh refers to Imam 'Ashim al-Kufi narrated by Imam Hafs. Many methods of reading the Qur'an have emerged, for example Al-Baghdadi, Iqro', Qiroati, Yanbu'a, Ummi, or others that have their own foundations and refer to qiro'at masyhuroh, so it becomes important for educational institutions to choose the right tahsin standards in order to better measure the final achievement of graduates. This study aims to describe the implementation of the Tahsin Standardization program for teachers to boost the pass rate of student tahsin exams at SDIT Salsabila 2 Klaseman which is still relatively low. The hope is to be able to be an inspiration for educational institutions or educational activists who have the same problem. This research is a type of case-based qualitative descriptive research. The subjects of his research were principals, salaried teachers and tahsin examining teachers. Data collection is carried out by means of observation, interviews and documentation. The results showed that all salaried teachers and tahsin examiners were gathered for deliberations to determine school tahsin standards. After that, the Tahsin Standardization program was implemented for each teacher to pay once a week to the tahsin examiner teacher. Time to adjust the teacher's blank hours. This program makes the frequency of tahsin of all teachers the same as the examiner so that it can boost the pass rate of students during the tahsin exam